Modifikasi Algoritme Bellman-Ford Untuk Pencarian Rute Terpendek Berdasarkan Kondisi Jalan - Yaddarabullah Yaddarabullah (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2019)
The application of the Bellman-ford algorithm for finding the shortest path both weighted and unweighted graph has a weakness in determining the shortest path based on road conditions. This study modified the Bellman-Ford algorithm by adding the Technique for Order of Preference by Similarity to the Ideal Solution method to provide alternative road assessments based on its condition criteria including road density, road width, travel time, and distance. This modified Bellman-Ford has better performance in finding the alternative shortest path by choosing a road with smoother conditions, even though distance and travel time increase.